Coordination Reactions and Noncovalent Interactions of Polyamines with Nucleotides in Binary Systems and with Nucleotides and Copper(II) Ion in Ternary Systems - Lechoslaw Lomozik; Anna Gasowska; Grzegorz Krzysko; Romualda Bregier-Jarzebowska (Bioinorganic Chemistry and Applications)
Interactions of nucleotides (AMP, CMP) and 1,2-diaminopropane (tn-1) or 2-methyl-1,2-diaminopropane (tn-2) in metal-free systems as well as in the systems including copper(II) ions were studied. The composition and overall stability constants of the complexes formed were determined by the potentiometric method, whereas the interaction centres and coordination sites were identified by spectroscopic methods. It was found that phosphate groups of nucleotides and the protonated amine groups of polyamines are the centres of interaction. The differences in the interactions with the polyamines which act as models of biogenic amines are impacted by the presence of lateral chains (methylene groups) in tn-1 and tn-2. In the ternary systems with Cu(II) ions, the heteroligand complexes are mainly of the ML⋯L’ type, in which the protonated polyamine is engaged in noncovalent interactions with the anchoring Cu(II)-nucleotide complex. The complexes formed in the Cu/NMP)/tn-1 system are more stable than those formed in the system with tn-2. The mode of coordination in the complex is realised mainly through the phosphate groups of the nucleotide with involvement of the endocyclic nitrogen atoms in a manner which depends upon the steric conditions and in particular on the number of the methylene groups in the polyamine molecule.